(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Among the Indian nationalists of his day, M.N. Roy stood out as one of the most intriguingradicals. He made an effort to bring together ideas from the rationalist renaissance, physical realism incosmology, humanist ethics, and a fierce pursuit of personal autonomy. One of the most influential Indianphilosophers of the twentieth century was M. N. Roy. Known as the Father of Indian Communism and thefirst revolutionary leader of India, he gained widespread recognition. Rabindranath’s thoughts had atremendous impact on social reform and equality. The reach of Tagore’s literature is vast. The ideal worldfor him combines rural living with a worldwide university, but without desensitizing the countries, cities,and profit systems. In reality, Tagore didn’t provide us a new world, but rather a plethora of lensesthrough which to examine the one we now inhabit. In terms of nationalist thought, Tagore was decadesahead of his time and deserves widespread exposure. These analyses compare and contrast theperspectives of M. N. Roy and Rabindranath Tagore on Indian society, as well as describing the former’spolitical ideas on freedom and the latter.